Comparison of shear bond strength of two porcelain repair systems after different surface treatment - Kalra, Ashish (Contemp Clin Dent, 2015)
INTRODUCTION: Intraoral chair side porcelain repair system is a quick, painless and highly patient acceptable procedure, without removal of restoration or fabrication of new restoration. There are very limited studies conducted to evaluate the shear bond strength of repair systems after different surface treatment. OBJECTIVES OF RESEARCH: The objective of research was to evaluate the shear bond strength of two intraoral porcelain repair systems Clearfil repair system (Kuraray) and Ceramic repair system (Ivoclar) to repair metal-ceramic restoration after three different surface treatment. MATERIALS AND METHODS: Totally, 120 discs of base metal alloy were fabricated. The opaque, dentine and enamel of ceramic were applied to achieve the uniform thickness. Defect was created, and repair was done using two repair systems after different surface treatment. Shear bond strength was measured. RESULTS: Analysis of variance was utilized. Ceramic repair system after 40% phosphoric acid surface treatment showed the highest mean value and Clearfil repair system after surface treatment with 37% phosphoric acid showed the lowest. The statistical difference was found to be significant between the groups. CONCLUSION: The shear bond strength of Ceramic repair system with 40% phosphoric acid etching showed highest shear bond strength as compared to other system and surface treatment used in the study.